Comparing is code specified flexural strength of concrete with split tensile strength by conducting test on cubes - M, Usha; Poluraju, P (International Journal of Engineering and Technology, 2018)
The present study aims at investigating the Code IS 456 specified flexure strengths of concrete. This investigation involved carrying out a split tensile test on cubes. The design mix calculations for M20, M25, M30, M40, M50 and M60 were done. Steel fibers were used to improve the resistance of fracture and tensile strength of concrete by its volume percentage of 1%, 2% and 3% for all the grades. The testwas carried out on the universal testing machine using billets to apply point load on exactly mid of the cube. It was observed that the code specified flexure strength is a conservative estimate.Â